Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
-cot(x)*csc(x) = zero
minus cotangent of (x) multiply by csc(x) equally 0
minus cotangent of (x) multiply by csc(x) equally zero
-cot(x)csc(x) = 0
-cotxcscx = 0
Similar expressions
cot(x)*csc(x) = 0
-cot(x)*cosec(x) = 0
-cot(x)*cosecx = 0
-cot(x)*csc(x) = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]